2018
DOI: 10.1002/jsfa.9272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of freezing on the bioaccessibility of beetroot (Beta vulgaris) bioactive compounds during in vitro gastric digestion

Abstract: From the treatments tested in this study, freezing with liquid nitrogen resulted in the greatest increase in bioaccessibility of the antioxidant and phenolic compounds of beetroots. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Several studies are available so far for beetroot phytochemicals digestibility [Dalmau et al, 2019;Guldiken et al, 2016;Tesoriere et al, 2008]. The processing method and the interactions with the food matrix are considered as the two external factors that signi cantly in uence the actual bioaccessibility and bioavailability of ingested phenolics [Shahidi & Peng, 2018].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies are available so far for beetroot phytochemicals digestibility [Dalmau et al, 2019;Guldiken et al, 2016;Tesoriere et al, 2008]. The processing method and the interactions with the food matrix are considered as the two external factors that signi cantly in uence the actual bioaccessibility and bioavailability of ingested phenolics [Shahidi & Peng, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…The processing method and the interactions with the food matrix are considered as the two external factors that signi cantly in uence the actual bioaccessibility and bioavailability of ingested phenolics [Shahidi & Peng, 2018]. Overall, a limited recovery for different beetroot products is reported that could be moderated by the pretreatment conditions [Dalmau et al, 2019;Guldiken et al, 2016]. So far, a lack of critical data about beetroot juice digestibility is noticeable.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that external factors, such as drying and digestion, can also have a significant impact on bioactivity. Similarly, Dalmau and coworkers hypothesized that the drying process might alter the microstructures of vegetables as they found that both convective drying (CD) and freeze-drying (FD) decreased the TPC and antioxidant activity of beetroot samples [ 129 ]. The authors, however, claimed that these drying processes facilitate the better release of bioactive compounds during the digestion process and, in turn, lead to higher TPC and antioxidant activities [ 129 ].…”
Section: Antioxidant Activity Of Selected Prominent Foodsmentioning
confidence: 99%
“…It was found that fresh, dried, and pureed beetroot exhibited the highest TP (total phenolic), TF (total flavonoid), and TAC (total antioxidant capacities) values. In recent years, it was then reported that freezing with liquid nitrogen resulted in greatest increase in TP of beetroot (Dalmau et al., 2019 ). Anne Porto Dalla Costa et al pointed out that beetroot waste flour was a convenient processing method.…”
Section: Biological Activitymentioning
confidence: 99%